Clinical and genetic characteristics of the syndrome of contractures of the limbs and face, hypothony and psychomotor retardation (OMIM: 616 266), caused by mutations in the NALCN gene - A. O. Borovikov; I. V. Sharkova; O. P. Ryzhkova; A. L. Chukhrova; O. A. Schagina; T. V. Markova; E. L. Dadali (Нервно-мышечные болезни, 2019)
A description of the clinical and genetic characteristics of the syndrome of congenital contractures of the limbs and face in combination with muscular hypotonia and psychomotor retardation of 2 patients from Russia is presented. As a result of full-exome DNA sequencing, 2 heterozygous missense mutations c 4355T C and c.3541C G were found in the NALCN gene, leading to amino acid substitutions at the functionally important center of the protein molecule. The effect of identified mutations in the NALCN gene on the function of its protein and approaches to the differential diagnosis of congenital contracture syndrome of the extremities and face in combination with muscular hypotonia and psychomotor retardation with monogenic variants of distal arthrogryposis with autosomal dominant type of inheritance are discussed.